Thermogravimetric investigations of cream with minoxidil - I. V. Gnitko; I. I. Berdei; V. V. Gladishev; B. S. Burlaka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Minoxidil is one of the most effective and modern medications, which is used in modern trichology for hair growth stimulation in case of androgenic and other forms of alopecia. Clinical effect of this substance is caused by the intensification of metabolic processes in the skin due to intensification of microcirculation. For local application domestic dermatology uses imported minoxidil medicines in form of alcohol-water lotions and aerosols.